2021
DOI: 10.1103/physrevapplied.16.034040
|View full text |Cite
|
Sign up to set email alerts
|

Pore-Size Measurement from Eigenvalues of Magnetic Resonance Relaxation

Abstract: Nonground eigenvalues are widely disregarded in magnetic resonance relaxation measurements of porous media due to difficulties involved in their measurement, detection, and the derivation of physically meaningful parameters from them. Such nonground eigenvalues may be experimentally observed in relaxation measurements, such as the relaxation correlation of T 1 − T 2 , and yield information on the pore size and surface relaxivity of porous media without calibration through other independent measurements. Nongro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…For comparison, the identified values for surface relaxivity are close to the reported ρ 2 = 8.0 μm/s for Bentheimer sandstone determined using the Bayesian MR approach by comparing the T 2 distribution and pore size distribution (Holland et al, 2013), but are smaller than the reported ρ 2 = 26 μm/s for Bentheimer sandstone Afrough et al (2021). The latter 2-3 times higher value is mainly due to the planar geometry assumed in their work, which provides less surface area per volume compared to spherical geometry.…”
Section: Predicted Nmr Parameterssupporting
confidence: 73%
See 1 more Smart Citation
“…For comparison, the identified values for surface relaxivity are close to the reported ρ 2 = 8.0 μm/s for Bentheimer sandstone determined using the Bayesian MR approach by comparing the T 2 distribution and pore size distribution (Holland et al, 2013), but are smaller than the reported ρ 2 = 26 μm/s for Bentheimer sandstone Afrough et al (2021). The latter 2-3 times higher value is mainly due to the planar geometry assumed in their work, which provides less surface area per volume compared to spherical geometry.…”
Section: Predicted Nmr Parameterssupporting
confidence: 73%
“…Consequently, if the assumptions leading to Equation are violated and, for example, there is higher susceptibility contrast around a pore resulting in larger internal gradients, larger values of ρ 2 will compensate for the resultant faster relaxation (Duschl et al., 2015; Stingaciu et al., 2010). Alternate 1D and 2D NMR methods based on the Decay due to Diffusion in the Internal Field (DDIF) technique (Song et al., 2002), or similar in nature, were proposed to measure pore‐size distributions of sedimentary rock, though constant pore shape and uniform constant surface relaxivity again are limiting assumptions (Afrough et al., 2021; Liu et al., 2014; Muncaci & Ardelean, 2013; Zhang et al., 2016).…”
Section: Introductionmentioning
confidence: 99%